Survival of Lactobacillus plantarumU40 on the in vitro rumen fermentation quantified with real-time PCR - Astuti, W.D.; Widyastuti, Y.; Wina, E.; Suharti, S.; Ridwan, R.; Wiryawan, K.G. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The objective of this study was to evaluate the survival of L. plantarumU40 quantified with real-time PCR during in vitro rumen fermentation. The experiment was arranged in a randomized block design with 3 treatments and 4 replications. Treatments were control, rumen fermentation inoculated with L. plantarumU40and L. plantarumU40 + glucose solution. Population of L. plantarum U40 was higher at inoculation treatment. After 8 hours incubation, glucose addition tended to decrease L. plantarum U40 population. Control treatment showed lowest population of L. plantarum U40 along in vitro fermentation compared with other treatment. Inoculation of L. plantarumU40 significantly (p<0.05) increased population of LAB until 12 hours incubation compared with control. Control treatment had highest pH at all incubation time. Glucose addition significantly (P<0.05) decreased final rumen pH (24 hours) (6.30), compared with control treatment (6.85). Inoculation of L. plantarum U40 with glucose addition significantly (P<0.05)increased propionic acid, decreased acetic acid and A/P ratio compared with other treatments. Lactobacillus plantarum U40 without glucose addition did not affect propionic acid production significantly. As conclusion, Lactobacillus plantarum U40 can survive in rumen fluid and changes rumen fermentation when glucose is added as carbon source.